Biodistribuição do fluconazol marcado com 99m tecnécio, livre e encapsulado em nanocápsulas, em um modelo experimental de infecção com Candida Albicans - Danielle Nogueira de Assis (2007)
Several classes of antifungal agents have been used in the treatment ofcandidiasis, but patients with advanced immunodeficiency may presentunsatisfactory results after therapy. In these cases, high doses of drugs or the multiple agents may sometimes be used, increasing the risk of serious side effects. Considering theses difficulties, the encapsulation of antifungal agents in nanoparticulate carriers has been used with the objective of modify the pharmacokinetic parameters of drugs, became the treatments more efficient and with less side effects. The purpose of this work was to evaluate the biodistribution of free 99mtechnetium labeled fluconazole and of that encapsulated in conventional and furtive nanocapsules, using Candida albicans as an infection model. The labeling of fluconazole with 99mTc was evaluated by thin layer chromatography. The labeling stability of 99mTc-fluconazole wasinvestigated in plasmatic medium. The size, homogeneity and zeta potential of NC preparations were determined with a Zetasizer 3000 HS (Malvern Instruments, UK). The morphology and the structural organization were evaluated by atomic force microscopy (AFM). The in vitro release study of NCs was evaluated in 0,9% NaCl and in 70% mice plasma. Male Swiss mice weighing between 20 and 25 g were used for the development of infectious foci induced by Candida albicans and for biodistribution studies. The labeling yield of fluconazole with 99mTc was 94% and the radiolabeled drug was stable for up 24 hours. The percentage of encapsulation of 99mTc-fluconazole in conventionaland furtive NCs was approximately 30%. The average diameter calculated by photon correlation spectroscopy (PCS) varied from 236 to 356 nm, while the average diameter determined by AFM varied from 238 to 411 nm. The diameter/height ratio decreased significantly when glutaraldehyde (25%) was used for fixation of NCs. The zeta potential varied from -55 to -69 nm and furtive NCs presented lower absolute values than conventional NCs. The in vitro release of 9mTc-fluconazole by the conventional and furtive NCs was greater in plasma medium than in 0,9% NaCl. The drug release from conventional NCs in plasma medium was faster than for furtive NCs. The histological and 99mTcfluconazoleuptake studies showed that infectious foci induced by 108 UFC/mLDanielle Nogueira de Assis xiv of C. albicans at 48 hours presented a more intense inflammatory process than the foci at 24 hours, which were induced by 106 UFC/mL. The biodistribution studies showed that free 99mTc-fluconazole was more rapidly eliminated by renal systems than the drug encapsulated in NCs. There were reduced levels of free99mTc-fluconazole at blood, 240 minutes after injection, while that the 99mTcfluconazole encapsulated in NCs remained in circulation at in significantly higher levels (P < 0,05). The uptake of conventional NCs by the mononuclear phagocyte system was greater than that for furtive nanocapsules. The nanocapsules remained in the infectious foci for a longer time than free 99mTcfluconazole. The results obtained suggesting that the nanocapsules could contribute for a longer retention of the drug in the infectious foci.